Technology assessment for an inventory management process in a hospital unit (2009)
The penetration of Auto Identification and Data Capture Technology (Auto ID DC) in healthcare logistics is low. A recent American Health Association ( AHA) study shows that 16% of hospitals use barcode technology for supply chain management purposes, and 3% use Radio Frequency Identification (RFID). Hospital materials managers find it difficult to evaluate the impact of Auto ID DC technologi es on current processes in or der to make a decision about whether or not to adopt a technological alternative. This paper studies the impact of Auto ID DC technologies on the inventory management process in a hospital unit. In particular we will refer to implantable devices within a catheterization lab. We propose a conceptual design of the system and a quantitative modeling approach to handle these issues, and present our preliminary results from a spreadsheet-based tool.